PENGARUH PENERAPAN KESEHATAN DAN KESELAMATAN KERJA TERHADAP KECELAKAAN KERJA KARYAWAN - Lira Agushinta; Ratu Anggun Kusuma Wijaya (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2016)
PT. DHL Exel Supply Chain Indonesia (Kraft Project) is a private company focused on domestic and international delivery and logistics. The company thinks that qualified human resources are important and needed that is the reason why they implement health and work safety procedure to decrease accidents at work. Using simple linear regression analysis and coefficient correlation, the research shows that the implementation of health and work safety contribute 56.4 % to the accident at work. Other factors, 43.6 %, are due to employees’ training, maintenance of operational equipment, and clean and neat work environment.